2018
DOI: 10.1002/jsfa.8990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cultivar and of conventional and organic agricultural practices on phenolic and sensory profile of blackberries (Rubus fruticosus)

Abstract: The effect of agricultural practices on the blackberries' chemical and sensory profile was dependent on the variety and cannot be generalized. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…This conclusion is consistent with the work of a number of scientists. For example, scientists from Portugal have shown that it is the characteristics of the variety that significantly affect the chemical composition and sensory profile of blackberries, and not the method of organic or traditional farming [2]. Researchers from Oregon noted that the amount of sugars is mainly influenced by the variety [3], our experience also confirmed this (96% of the variation in the trait is due to the influence of the variety).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This conclusion is consistent with the work of a number of scientists. For example, scientists from Portugal have shown that it is the characteristics of the variety that significantly affect the chemical composition and sensory profile of blackberries, and not the method of organic or traditional farming [2]. Researchers from Oregon noted that the amount of sugars is mainly influenced by the variety [3], our experience also confirmed this (96% of the variation in the trait is due to the influence of the variety).…”
Section: Discussionsupporting
confidence: 64%
“…Fruiting, as a rule, occurs on the shoots of the second year, after which they die off [1]. Currently, consumer demand for blackberries is growing, due to the fact that a number of studies have shown it as a source of biologically active substances with high antioxidant activity [2][3][4][5]. In Russia, blackberries bear fruit later than traditional berry crops, and, therefore, they can occupy a niche in the supply chain of seasonal berries in the domestic market.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, few correlations were found between sensory descriptors and higher presence of bioactive compounds (polyphenols and anthocyanins), except for a decreased intensity of salted taste. The multivariate analyses (e.g., PCA or PLS regression) are increasingly used in the sensory science in the attempt of highlighting the degree of contribution of each interdependent sensory attribute to the overall variability of data, or assessing the correlation between the sensory attributes and the analytical data [99][100][101][102][103][104].…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…24 Also, agricultural practices which may vary across geographic regions may influence phenolic composition; organic practices have been shown to yield blackberries with higher phenolic content than conventional farming practices. 25 The wide variability in flavonoid composition in berries and their processed forms should be considered in clinical studies, especially in the interpretation of effects on clinical outcomes.…”
Section: Nutritional Value Of Dietary Berriesmentioning
confidence: 99%